The response of the algae Fucus virsoides (Fucales, Ochrophyta) to Roundup® solution exposure: A metabolomics approach. (November 2019) - Felline, S.; Del Coco, L.; Kaleb, S.; Guarnieri, G.; Fraschetti, S.; Terlizzi, A.; Fanizzi, F.P.; Falace, A.
Abstract: Glyphosate, as a broad-spectrum herbicide, is frequently detected in water and several studies have investigated its effects on several freshwater aquatic organisms. Yet, only few investigations have been performed on marine macroalgae. Here, we studied both the metabolomics responses and the effect on primary production in the endemic brown algae Fucus virsoides exposed to different concentration (0, 0.5, 1.5 and 2.5 mg L −1 ) of a commercial glyphosate-based herbicide, namely Roundup®. Our results show that Roundup® significantly reduced quantum yield of photosynthesis (Fv /Fm ) and caused alteration in the metabolomic profiles of exposed thalli compared to controls. Together with the decrease in the aromatic amino acids (phenylalanine and tyrosine), an increase in shikimate content was detected. The branched-amino acids differently varied according to levels of herbicide exposure, as well as observed for the content of choline, formate, glucose, malonate and fumarate. Our results suggest that marine primary producers could be largely affected by the agricultural land use, this asking for further studies addressing the ecosystem-level effects of glyphosate-based herbicides in coastal waters. Graphical abstract: Image 1 Highlights: The effects of glyphosate-based herbicide (GBH) on Fucus virsoides were tested. We showed a relation between glyphosate accumulation and physiological responses. Both the photosynthetic efficiency and metabolism of Fucus were affected by GBH. For the first time, the involvement of shikimate pathway was shown in brown algae. The herbicides might drive the reduction of marine macroalgal communities. Abstract : Glyphosate-based herbicide (GBH) effects on metabolic profiles of brown algae Fucus virsoides .